Gadolinium(III)-Based Dual H-1/F-19 Magnetic Resonance Imaging Probes - Pujales Paradela, Rosa; et al. (Chemistry - A European Journal, 2019)
We present two novel octadentate cyclen-based ligands bearing one (L-1) or two (L-2) phenylacetamide pendants with two CF3 groups either at positions 3 and 5 (L-1) or 4 (L-2). The corresponding Gd3+ complexes possess one coordinated water molecule, as confirmed by luminescence lifetime measurements on the Eu-III and Tb-III analogues. A detailed H-1 and O-17 relaxometric characterization has revealed the parameters that govern the relaxivities of these complexes. The water-exchange rate of the mono-amide derivative GdL1 (k(ex)(298) =1.52 x 10(6)s(-1)) is faster than that determined for the bis-amide complex GdL2 (k(ex)(298) = 0.73 X 10(6)s(-1)). H-1 and F-19 NMR studies have indicated that the complexes are present in solution almost exclusively as the square-antiprismatic (SAP) isomers. F-19 NMR relaxation studies indicated Gd...F distances of 7.4 +/- 0.1 and 9.1 +/- 0.1 angstrom for GdL1 and GdL2, respectively. Phantom MRI studies revealed the favorable properties of GdL2 as a dual (1)(H)/F-19 magnetic resonance imaging (MRI) probe, whereas the shorter Gd...F distance of GdL1 reduces the signal-to-noise ratio due to the very short transverse relaxation time of the F-19 NMR signal.
Keywords: fluorine; gadolinium; macrocycles; magnetic resonance imaging (MRI); NMR spectroscopy